The balance of payments as a monetary phenomenon - a review and consideration of Irish evidence 1960-1978 - Kenneally, Martin; Finn, Mary (Economic & Social Studies, 1985)
This paper briefly sketches alternative approaches to balance of payments theory and notes the salient features of `the? monetary approach. Some alternative models associated with the monetary approach are distinguished and existing evidence relating to them is reviewed. Annual and quarterly Irish evidence for these models over the period I960-1978 are presented and assessed and some policy conclusions are offered.
Keywords: Economics - Ireland; Balance of payments - Ireland